Kompensasi Lingkungan Kerja dan Motivasi Terhadap Kinerja Pegawai PT Angkasa Pura 1 di Bandar Udara Adi Soemarmo - Risma Nur Pratiwi; Esti Dwi Rahmawati; Agus Suyatno (Journal of Management and Creative Business, 2024)
Study This aim For analyze role mediation motivation work on influence compensation and environment Work to performance employee of PT Angkasa Pura 1 Adi Soemarmo Airport Branch Office . Population in study This is employee employees of PT Angkasa Pura 1 Adi Soemarmo Airport Branch Office who work more of 1 ( one ) year and amount sample in study This as many as 87 respondents . Variables used​ in study This is compensation , environment work , motivation work and performance employee . Data used in study This in the form of primary data. Data collection methods used is questionnaire . Data analysis techniques used is Structural Equation Modeling -Partial Least Square (SEM-PLS) and using the SmartPLS 4.0 program . Research result This show that compensation influential positive and significant to motivation work , environment Work influential positive and significant to motivation work , compensation influential positive and significant to performance employees , environment Work influential positive and significant to motivation work , motivation Work influential positive and significant to performance employees , compensation influential positive and significant to performance employee through motivation Work as intervening variables , as well environment Work influential positive and significant to performance employee No through motivation Work as intervening variable .